Guidelines for the diagnosis, prevention and treatment of osteoporosis - M. Rossini; G. Rini; R. Nuti; S. Minisola; S. Migliaccio; C. Mereu; L. Masi; C. Marcocci; E. Mannarino; G. Luisetto; G.C. Isaia; S. Gonnelli; et al. (PAGEPress Publications, 2011)
The guidelines for the osteoporosis management were first drafted by a working group and then critically evaluated by the board of SIOMMMS. The most relevant points are: Definition: Osteoporosis is defined as a quantitative and qualitative deterioration of bone tissue leading to increased risk of fracture. Postmenopausal and senile osteoporosis are defined as primitive. Diagnosis: The cornerstone for the diagnosis of osteoporosis is the measurement of bone mineral density (BMD) by DXA (dual-energy X-ray absortiometry) at the femoral neck with T-score values <-2.5, following the WHO definition. Other DXA sites or technologies for measuring bone mass are also acceptable when the former is not accessible. A BMD evaluation is recommended to all women above 65 years of age. At younger age or in man the bone assessment is recommended only in subjects with specific risk factors. A control of bone mass measurement is seldom required before 2 years. Differential diagnosis: A few biochemical tests such as serum and urinary calcium, protein electrophoresis, serum creatinine and ESR are usually sufficient to exclude most secondary types of osteoporosis. The value of the so called bone turnover markers for the diagnosis and follow-up of osteoporosis remains uncertain. Several secondary forms of osteoporosis require a specific diagnostic and therapeutic management. Prevention: The osteoporosis prevention should be based on the elimination of specific risk factors such as inadequate calcium and vitamin D intake, smoking and sedendary life. The use of pharmacological agents in subjects with BMD values >-2.5 is usually not justified. Pharmacological intervention: The use of drugs registered for the treatment of osteoporosis are recommended when the benefits overcome the risk. This is the case only when the risk of fracture is rather high. FRAX™ is recognized as a useful tool for easily estimate the long-term fracture risk. SIOMMMS with these guidelines is committed to validate and further develop this diagnostic tool.